DGAT1 and ABCG2 polymorphism in Indian cattle (Bos indicus) and buffalo (Bubalus bubalis) breeds - Tantia, Madhu S (BioMed Central, 2006)
BACKGROUND: Indian cattle (Bos indicus) and riverine buffalo (Bubalus bubalis) give a poor yield of milk but it has a high fat and protein percentage compared to taurine cattle. The identification of QTLs (Quantitative Trait Loci) on BTA14 and BTA6 and its subsequent fine mapping has led to identification of two non conservative mutations affecting milk production and composition. Our objective was to estimate the frequency of K232A (DGAT1 – diacylglycerol – acyltransferase 1) and Y581S (ABCG2 – ATP binding cassette sub family G member 2) polymorphisms in diverse cattle and buffalo breeds of India having large variation in terms of milk production. RESULTS: We screened the reported missense mutations in six cattle and five buffalo breeds. The DGAT1(K )and ABCG2(Y )alleles were found to be fixed in Indian cattle and buffalo breeds studied. CONCLUSION: This study provides an indirect evidence that all the Indian cattle and buffalo breeds have fixed alleles with respect to DGAT1 and ABCG2 genes reported to be responsible for higher milk fat yield, higher fat and protein percent.